Indole-3-acetic acid improves drought tolerance of white clover via activating auxin, abscisic acid and jasmonic acid related genes and inhibiting senescence genes - Zhang, Youzhi (BMC Plant Biol, 2020)
BACKGROUND: Auxin may have a positive effect on plants under drought stress. White clover is widely cultivated and often prone to water shortages. In the present study, we investigated the effects of exogenous indole − 3-acetic acid (IAA) on growth and physiological changes of white clover under drought stress condition. The contents of endogenous IAA and other hormones including ABA, CTK, JA, GA, IAA, and SA were assayed. Moreover, expressions of auxin-responsive genes, drought-responsive genes and leaf senescence-associated genes were detected in response to exogenous IAA. RESULTS: Compared to control, drought stress alone significantly diminished stem dry weigh, relative water content (RWC) and total chlorophyll content (Chl). Exogenous IAA treatment significantly increased RWC and Chl, whereas L-AOPP treatment drastically decreased stem dry weight, RWC and Chl under drought stress condition. Additionally, exogenous IAA treatment significantly increased ABA content and JA content, up-regulated expression of auxin responsive genes (GH3.1, GH3.9, IAA8), drought stress responsive genes (bZIP11, DREB2, MYB14, MYB48, WRKY2, WRKY56, WRKY108715 and RD22), and down-regulated expressions of auxin-responding genes (GH3.3, GH3.6, IAA27) and leaf senescence genes (SAG101 and SAG102) in the presence of PEG. Contrarily, L-AOPP treatment significantly reduced contents of ABA, GA3 and JA, down-regulated expressions of GH3.1, GH3.9, IAA8, bZIP11, DREB2, MYB14, MYB48, WRKY2, WRKY56, WRKY108715, ERD and RD22, and up-regulated SAG101 and SAG102. CONCLUSIONS: Exogenous IAA improved drought tolerance of white clover possibly due to endogenous plant hormone concentration changes and modulation of genes involving in drought stress response and leaf senescence. These results provided useful information to understand mechanisms of IAA improved drought tolerance in white clover.